UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL COOPERATIV TIPE SNOWBALLTHROWING PADA TEMA DAERAH TEMPATTINGGALKU KELAS IV SDN 106185TANJUNG GARBUS - Syahputri Nidiawan Baros (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This thesis examines the use of the snowball throwing learning model to improve student learning outcomes on the theme of the area where I live in class V SD Negeri 106185 Tanjung Garbus. Theories used include theories about learning, learning outcomes, factors that influence learning outcomes, learning models. The model used is a cooperative learning model of the snowball throwing type, which is a teaching model by making questions into paper where the paper will be made like a snowball. The results of research and discussion show that the use of the snowball throwing learning model in teaching can improve student learning outcomes in thematic lessons. in class IV SDN 106185 Tanjung Garbus, Pagar Merbau District, Deli Serdang Regency. The average value obtained by students in the first cycle is 66.6. Of the 21 students, 14 students (66.67%) have completed learning while 7 students (33.33%) have not finished studying. In the second cycle there was an increase in the average value to 83.8. Of the 21 students, 20 students (95.23%) have experienced mastery learning, while 1 student (4.77%) has not been completed. The average score obtained by students has reached the desired target, which is above 75. Where can seen from the average score of students in the initial conditions of 41.03 (51%) increased in the first cycle of 51.17 (64%) and increased again in the second cycle of 63.67 (80%).